2009
DOI: 10.1271/bbb.80449
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis G-Protein β-Subunit Is Required for Defense Response againstAgrobacterium tumefaciens

Abstract: Typical early pathogen-associated molecular pattern (PAMP) responses include the generation of reactive oxygen species (ROS) and MAP kinase (MAPK) activation, but little is known about the molecular mechanisms that link receptor activation to intracellular signal transduction. In this study, we found that in agb1-2 (AGB1 null mutation) mutants, ROS production triggered by flg22 or elf18 was significantly reduced and that elf18-stimulated PAMP-triggered immunity (PTI) against Agrobacterium tumefaciens was impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 35 publications
4
47
0
2
Order By: Relevance
“…The gene AGB1, encoding the b-subunit in Arabidopsis, is highly induced after flg22 and elf18 treatment (Zipfel et al, 2006). Based on this observation, Ishikawa (2009) investigated whether AGB1 is involved in FLS2-and EFR-mediated responses and showed that agb1 mutants are impaired in the oxidative burst and seedling growth inhibition triggered by flg22 and elf18. Similarly, XLG2 (for extralarge protein G 2) gene expression is induced after bacterial infection, and xlg2 mutant plants are more susceptible to P. syringae (Zhu et al, 2009).…”
Section: Heterotrimeric G Proteinsmentioning
confidence: 99%
“…The gene AGB1, encoding the b-subunit in Arabidopsis, is highly induced after flg22 and elf18 treatment (Zipfel et al, 2006). Based on this observation, Ishikawa (2009) investigated whether AGB1 is involved in FLS2-and EFR-mediated responses and showed that agb1 mutants are impaired in the oxidative burst and seedling growth inhibition triggered by flg22 and elf18. Similarly, XLG2 (for extralarge protein G 2) gene expression is induced after bacterial infection, and xlg2 mutant plants are more susceptible to P. syringae (Zhu et al, 2009).…”
Section: Heterotrimeric G Proteinsmentioning
confidence: 99%
“…These reactions comprise, among others, the influx of calcium (Ca 2+ ) ions from the apoplastic space, the extracellular accumulation of ROS, and the intracellular activation of mitogen-associated protein kinase cascades (Boller and Felix, 2009). Microbe-associated molecular patterninduced formation of hydrogen peroxide is severely compromised in agb1-2 mutant plants (Ishikawa, 2009), suggesting a link between AGB1 function and ROS accumulation. We exploited this phenotype to assess the capability of AGB1 mutant variants to complement the agb1 deficiency in ROS production.…”
Section: Ros Productionmentioning
confidence: 99%
“…The Arabidopsis agb1 null mutant shows reduced accumulation of reactive oxygen species (ROS) in response to microbial inducers such as bacterial flagellin and EF-Tu (Ishikawa, 2009). Moreover, agb1 null mutants are hypersensitive to the necrotrophic fungi Plectosphaerella cucumerina and Alternaria brassicicola and the hemibiotrophic fungus Fusarium oxysporum (Llorente et al, 2005;Trusov et al, 2006Trusov et al, , 2009Delgado-Cerezo et al, 2012).…”
mentioning
confidence: 99%
“…Resistance against other necrotrophic pathogens, such as Fusarium oxysporum, Alternaria brassicicola, and Botrytis cinerea, was also found to be compromised in AGB1-and AGG1/ AGG2-deficient mutants (Trusov et al, 2006(Trusov et al, , 2007(Trusov et al, , 2009). In addition, loss of function of the Gb subunit leads to reduced elf18-induced resistance against Agrobacterium tumefaciens as well as reduced reactive oxygen species (ROS) production triggered by flagellin22 (flg22) and elf18 (an 18-amino acid peptide that represents the N terminus of bacterial EF-Tu; Ishikawa, 2009). Multiple surface residues of AGB1 were recently shown to play important roles in resistance against necrotrophic pathogens and flg22-induced ROS production (Jiang et al, 2012).…”
mentioning
confidence: 99%